Modeling the action of anaerobic biofilm - Poliakov, V.L. (Доповіді НАН України, 2021)
A mathematical problem of the action of a representative biofilm in the absence of oxygen is formulated. The anaerobic process of decomposition of a dissolved organic matter is considered as a two-stage process, proceeding due to the vital activity of two groups of microorganisms. An approximate analytic solution allowing one to calculate the concentration and consumption of primary and secondary organic substrates with minimal errors has been obtained. On test examples, their rates of transfer through the biofilm surface are determined, and the possibility of the movement of volatile fatty acids in both directions is discussed.